2016
DOI: 10.1177/2047487316679905
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in physical activity following acute myocardial infarction in adults: A prospective, observational study

Abstract: Aims Despite the benefits of regular physical activity participation following acute myocardial infarction, little is known about gender differences in physical activity among patients after acute myocardial infarction. We described, by gender, physical activity trajectories pre- and post-acute myocardial infarction, and determined whether gender was independently associated with physical activity. Methods and results The Variation in Recovery: Role of Gender on Outcomes of Young AMI patients (VIRGO) study, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 43 publications
4
37
1
1
Order By: Relevance
“…This is in line with other studies conducting in other nations [26] [27]. Minges et al, [27] conducted an international prospective observational study with large sample size (n = 3572) in the USA, Australia and Spain to examine gender differences in physical activity after heart disease problem. The study reported male patients being more active than female patients at baseline, one month, and 12 months.…”
Section: Discussionsupporting
confidence: 82%
“…This is in line with other studies conducting in other nations [26] [27]. Minges et al, [27] conducted an international prospective observational study with large sample size (n = 3572) in the USA, Australia and Spain to examine gender differences in physical activity after heart disease problem. The study reported male patients being more active than female patients at baseline, one month, and 12 months.…”
Section: Discussionsupporting
confidence: 82%
“… 32 Our finding that maintenance of PA was 1.7 times more likely in men than women is similar to the findings from other studies that women are more likely to be inactive after a cardiac event. 33 Tailored interventions addressing the varied independent factors that affected our Chinese patients' participation in PA might be able to improve their maintenance of PA.…”
Section: Discussionmentioning
confidence: 99%
“…36, 53 Additionally young women are less likely to be taking statins at discharge and among those on statins, women are also less likely to be treated with a high intensity dose at 1-month post AMI, compared with men. 36 Beyond immediate management and medications, women are less likely to be counseled by physicians about lifestyle choices.…”
Section: Post-ami Carementioning
confidence: 99%